Effect of pH and concentration on physicochemical, adsorption kinetics and rheology properties of quinoa protein: Functional correlations - José Fernando Solanilla-Duque; Diego Fernando Roa-Acosta; Jesús Eduardo Bravo-Gómez (JCIS Open)
In the present manuscript protein isolates and hydrolysates have countless applications in the food industry due to their functional (solubility, emulsifying power, adsorption capacity, foaming capacity) and nutritional properties [1]. In the present manuscript, the interfacial, rheological, and functional properties of the quinoa protein isolate (QPI) at pH 5 and pH 7 were studied. Dilatational module behavior versus surface pressure was evaluated, using the Frumkin-Lucassen model for QPI, which showed a good fit in the first part of the curve (before achieving a plateau) evidencing the formation of the first interfacial layer. Moreover, the gel formation from QPI was evaluated at different concentrations (5, 10 and 15 % (w/w)). Rheological measurements indicated that higher protein concentrations at pH 5 resuts in a raise in the gel point temperature. It was also found that QPI showed better emulsifying and foaming capacity at pH 5 than at pH 7. An increase in the QPI concentration in the emulsion formulation produces greater thermal stability. The results obtained show the feasibility of using a quinoa protein isolate as an ingredient in functional foods (Modified (enriched or enhanced) foods, conventional foods, medicinal foods and foods for dietetic use.).